Complexation of Cm(III) with 6-(5,6-dipentyl-1,2,4-triazin-3-yl)-2,2′-bipyridine studied by time resolved laser fluorescence spectroscopy - Bremer, Antje; Geist, Andreas; Panak, Petra (Dalton transactions, 2012)
The complexation of Cm(III) with 6-(5,6-dipentyl-1,2,4-triazin-3-yl)-2,2′-bipyridine (C5-hemi-BTP) in a water-2-propanol solution is investigated by TRLFS. Upon increasing the concentration of C5-hemi-BTP in the Cm(III)-solution, three different species, the 1:1-, 1:2- and 1:3-complex, with emission bands at 599.9 nm, 607.3 nm, and 612.8 nm, respectively, are found. Hereby, slow complexation kinetics is observed which no other BTP-type ligand has shown up to now. The species distributions for various ligand concentrations are determined and stability constants are derived (log β03 = 12.1 ± 0.1). As extraction with hemi-BTP ligands is only possible in the presence of a lipophilic anion, the complexation of Cm(III) with C5-hemi-BTP and 2-bromohexanoic acid is investigated to deduce the species formed in the extraction process. It is found that Cm(III) is coordinated by two C5-hemi-BTP ligands and one 2-bromohexanoate ligand. This species formed in aqueous solution is identical to the one from the extraction process.
First published on 17 May 2012
Gesehen am 28.06.2018